Analisis Kelayakan Usaha Penyulingan Minyak Daun Cengkeh di Kelurahan Ulunggolaka Kecamatan Latambaga Kabupaten Kolaka - Husain, Muhammad; Limi, Muhammad Aswar; Sadimantara, Fahria Nadiryati (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
The purpose of this study was to analyze the financial feasibility of refining clove leaf oil in Ulunggolaka Village, Latambaga District, Kolaka Regency. The location of the study was determined intentionally, because the Ulunggolaka Village was one of the villages with the largest clove production in Latambaga District. The respondents who were selected purposively were business owners. Primary and secondary data collected were analyzed using financial feasibility methods including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), and Sensitivity Analysis. Calculation of financial feasibility criteria in clove leaf oil distillation business shows that the NPV for the period 2013 - 2018 is IDR 72,101,202 with IRR 19.84% and PBP for 3 years 2 days. Sensitivity analysis shows that by reducing production by 5%, the calculation of NPV and IRR shows a negative number, meaning that the effort is not feasible. But by increasing the cost of dry clove leaf raw materials by 5%, then the business of refining clove leaf oil is still feasible to run